Factors and Molecular Mechanisms Influencing the Protein Synthesis, Degradation and Membrane Trafficking of ASIC1a - Xu, Yayun; Chen, Feihu (Frontiers in Cell and Developmental Biology, 2020)
Acid-sensing ion channels (ASICs) are members of the degenerin/epithelial sodium channel superfamily. They are extracellular pH sensors that are activated by protons. Among all ASICs, ASIC1a is one of the most intensively studied isoforms because of its unique ability to be permeable to Ca2+. In addition, it is considered to contribute to various pathophysiological conditions. As a membrane proton receptor, the number of ASIC1a present on the cell surface determines its physiological and pathological functions, and this number partially depends on protein synthesis, degradation, and membrane trafficking processes. Recently, several studies have shown that various factors affect these processes. Therefore, this review elucidated the major factors and underlying molecular mechanisms affecting ASIC1a protein expression and membrane trafficking.